Building Professional Teachers: Analysis of the Ability of Prospective Chemistry Teachers in Designing Discovery Learning-Based Learning Tools - Allo, Eda Lolo; Cahyani*, Vika Puji; Ruslan, Zuhrah Adminira; Jusniar, Jusniar; Nawi, Mohd Zulfakar Mohd (Jurnal Pendidikan Sains Indonesia, 2025)
Several studies have emphasised the value of discovery learning in enhancing students' understanding of chemical concepts and improving their critical thinking skills. However, research on the skills or competencies of prospective chemistry teachers in developing discovery learning based instructional materials remains limited, particularly in the context of higher education in indonesia. This study aims to evaluate the relationship between the quality of student worksheets, the quality of teaching materials, and the quality of teaching modules with the ability to develop instructional tools. The research employed the structural equation modelling-partial least squares (SEM-PLS) method using smart PLS software to examine the correlation between the quality of instructional materials and the ability of prospective chemistry teachers to design learning tools. The collected instructional materials were evaluated using an assessment rubric. The results of hypothesis testing through bootstrapping showed that the quality of student worksheets had a positive and significant effect on the ability to develop instructional tools (p = 0.002). Similarly, the quality of teaching materials significantly influenced the ability to design instructional tools (p = 0.000). Furthermore, the quality of teaching modules also significantly affected the ability to construct instructional tools (p = 0.001). These findings indicate a complex and interconnected relationship between the quality of learning components such as student worksheets, teaching materials, and teaching modules and the competence to develop effective learning tools